2012
DOI: 10.1002/eji.201142088
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the adenosine A2A receptor attenuates experimental autoimmune myasthenia gravis severity

Abstract: The adenosine A2A receptor (A2AR) is the major cellular adenosine receptor commonly associated with immunosuppression. Here, we investigated whether A2AR activation holds the potential for impacting the severity of experimental autoimmune myasthenia gravis (EAMG) induced following immunization of Lewis rats with the acetylcholine receptor (AChR) R97-116 peptide. This report demonstrates reduced A2AR expression by both T cells and B cells residing in spleen and lymph nodes following EAMG induction. A2AR stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…A 2A receptors have a well described immunossupressive action on immune cells [47] and their activation has proven beneficial in neuromuscular inflammatory diseases such as experimental auto-immune myasthenia gravis [48]. Schwann cells participate in adenosinergic modulation at the level of the neuromuscular junction [49] and can also participate in the modulation of immune actions [50].…”
Section: Discussionmentioning
confidence: 99%
“…A 2A receptors have a well described immunossupressive action on immune cells [47] and their activation has proven beneficial in neuromuscular inflammatory diseases such as experimental auto-immune myasthenia gravis [48]. Schwann cells participate in adenosinergic modulation at the level of the neuromuscular junction [49] and can also participate in the modulation of immune actions [50].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the serum ADA activity should be investigated in more MG patients. Li et al [45] reported a reduction of A2AR expression in both T cells and B cells residing in spleen and lymph nodes following EAMG induction. A2AR stimulation inhibited anti-AChR antibody production and proliferation of AChR-specific lymphocytes in vitro.…”
Section: Adenosine Pathway Changes In Human Autoimmune Diseasesmentioning
confidence: 99%
“…The A2A receptors also decrease chemokine receptor, dendritic cells, and T cell expression levels [31,35]. It has also been reported that A2A receptor treatment is for several disorders such as autoimmune inflammation, Parkinson's disease, and experimental autoimmune encephalomyelitis [36,37].…”
Section: Introductionmentioning
confidence: 99%